2021
DOI: 10.1186/s12917-021-02810-3
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial use and resistance in Escherichia coli from healthy food-producing animals in Guadeloupe

Abstract: Background Selection pressure exerted by use of antibiotics in both human and veterinary medicine is responsible for increasing antimicrobial resistance (AMR). The objectives of this study were to better understand antimicrobial use in pigs, beef cattle, and poultry on farms on Guadeloupe, French West Indies, and to acquire data on AMR in Escherichia coli in these food-producing animals. A cross-sectional survey was conducted at 45 farms on Guadeloupe, and practical use of antimicrobials was do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…Tetracycline resistance is often found in ESBL-producing isolates and transmitted with ESBL containing plasmids [86]. In contrast, Gruel et al [33] reported that the use of tetracycline is not correlated to ESBL-producing E. coli. Although tetracycline is not listed as critically important for human treatment [20], there is a great concern since it can promote resistance to other antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tetracycline resistance is often found in ESBL-producing isolates and transmitted with ESBL containing plasmids [86]. In contrast, Gruel et al [33] reported that the use of tetracycline is not correlated to ESBL-producing E. coli. Although tetracycline is not listed as critically important for human treatment [20], there is a great concern since it can promote resistance to other antimicrobials.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, despite rational use of antimicrobials, the rate of ESBL-producing E. coli in livestock, although moderate, is of concern [ 33 ]. Fewer data are available on ESBL-producing K. pneumoniae , since most of the studies are related to ESBL-producing E. coli .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The University Hospital of Guadeloupe faced the emergence of carbapenemase-producing Enterobacteriaceae isolates and a very high incidence of nosocomial ESBL-E infections ( Bastian et al, 2015 ; Breurec et al, 2015 ; Le Terrier et al, 2021 ). A moderate prevalence of ESBL-E (around 5%) was observed in studies on community human urinary tract infections ( Guyomard-Rabenirina et al, 2016 ), on fecal carriage by domestic animals and livestock ( Gruel et al, 2021 ) and on wild fauna ( Guyomard-Rabenirina et al, 2020 ). Guadeloupe is an ideal place to study the circulation of multi-resistant bacteria and resistance genes because of its insularity and small population (395,700 inhabitants) and area (1,436 km 2 ).…”
Section: Introductionmentioning
confidence: 99%